Determination Of Debt Covenant, Leverage , Financial Distress Against Accounting Conservatism - Efendi, Mohamad Johan; Huda, Khasbulloh; Sholeh, Rachmad; Waluyo, Sugeng Eko Yuli (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
The objective of this research is to examine the impact of financial hardships, debt covenants, and leverage on accounting conservatism in a partial and simultaneous manner. The analysis focuses on firms operating in the industrial and consumer products sectors, which are listed on the Indonesia Stock Exchange (IDX) during the period from 2016 to 2020. This particular research methodology employs quantitative techniques to investigate a predefined population or sample. The samples were obtained using a purposive sampling strategy, which included selecting individuals based on preset criteria. This study uses data regression analysis as a method of data analysis, using the SPSS software. The findings indicated that accounting conservatism was only partly unaffected by financial troubles. Debt covenants have a partial influence on accounting conservatism, while leverage partly has a notable impact on accounting conservatism. Furthermore, accounting conservatism is significantly affected by a combination of financial challenges, debt covenants, and leverage.